2016
DOI: 10.1093/annonc/mdw150
|View full text |Cite
|
Sign up to set email alerts
|

Primary analysis of a prospective, randomized, single-blinded phase II trial evaluating the HER2 peptide AE37 vaccine in breast cancer patients to prevent recurrence

Abstract: The overall intention-to-treat analysis demonstrates no benefit to vaccination. However, the results confirm that the vaccine is safe and suggest that vaccination may have clinical benefit in patients with low HER2-expressing tumors, specifically TNBC. Further evaluation in a randomized trial enrolling TNBC patients is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 17 publications
3
64
0
2
Order By: Relevance
“…The HER2-specific vaccine nelipepimut-S (HER2 369-377, E75, NeuVax) is a human leukocyte antigen (HLA) A2 restricted, major histocompatibility complex (MHC) class I, dominant epitope derived from the extracellular domain of HER2, and has been evaluated in the adjuvant setting to prevent breast cancer recurrence in women rendered clinically disease-free after standard-ofcare therapy [7][8][9]. Nelipepimut-S induces a CD8+ cytotoxic T-lymphocyte (CTL) response to HER2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HER2-specific vaccine nelipepimut-S (HER2 369-377, E75, NeuVax) is a human leukocyte antigen (HLA) A2 restricted, major histocompatibility complex (MHC) class I, dominant epitope derived from the extracellular domain of HER2, and has been evaluated in the adjuvant setting to prevent breast cancer recurrence in women rendered clinically disease-free after standard-ofcare therapy [7][8][9]. Nelipepimut-S induces a CD8+ cytotoxic T-lymphocyte (CTL) response to HER2.…”
Section: Introductionmentioning
confidence: 99%
“…There was no demonstrable difference in 5-year overall diseasefree survival (DFS) in the intention-to-treat populations. However, there was evidence of benefit in subgroups of breast cancer patients [7,17,18]. Here, we present the final analysis of the primary endpoint of DFS with additional follow-up as well as additional per-treatment analysis, along with comprehensive pre-specified subset analyses for both the GP2 and AE37 peptide vaccines used in a randomized controlled trial of breast cancer patients with any level of HER2 expression that were clinically disease-free and at a high risk for recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…As seen in our previous study evaluating the E39 peptide vaccine, as well as our studies evaluating HER2-derived peptide vaccines, most of the toxicity experienced was skin reactions, to include erythema and pruritus, and mild flu-like symptoms [46, 10]. In several of our previous randomized, controlled trials, control patients have received GM-CSF alone, and we have seen similar rates of systemic toxicity between vaccine and control arms, implying that the toxicity from the peptide vaccines is related to the GM-CSF, not the peptide itself [4, 5]. Therefore, although this trial did not have a GM-CSF only arm, it is reasonable to suggest that the toxicity seen is attributable to the adjuvant.…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, trastuzumab appeared to have clinical benefit despite the absence of HER2 overexpression in a subset analysis of this patient population. Although not statistically significant, another subset analysis from a randomized phase II trial of the HER2 peptide vaccine AE37 showed a trend toward improved disease‐free survival in TNBC patients with low‐level HER2 expression who received the vaccine compared with those who did not . Further data are needed to fully characterize the impact of HER2‐directed therapies in TNBCs, and the ongoing phase III NASBP B47 trial should provide more clarity in this area.…”
Section: Targeting the Subtypes Of Tnbc For Therapeutic Benefitmentioning
confidence: 97%